Changing Social Structures in Makassar City Due to Rapid Urbanization in South Sulawesi - Soraya, Tania; Camila, Sasqia Navla; Maulidia, Afriliya (Journal Social Civilecial, 2025)
This work then analyses the effects of urbanization on social organization, culture and identity of Makassar City South Sulawesi. This means that as the city expands socially as well as in terms of the conthe size of population and infrastructure development the existing social structure and norms and cultural practices are altering. The research questions refer to how urban growth has affected displacement, the level of social cohesiveness, and cultural cumendums within the community, a research approach that is purely qualitative in nature. Literature review was used to gather firsthand information from ten seniors’ residents of Plains, focused group discussions were conducted with senior urban planners and key leaders of Plains and to understand the perception regarding urbanization that is prevailing at Plains. Whereas one might have a positive perception of urban expansion as provider of jobs, hope for transformation and development; another may feel the urbanization is a curse to her community and environment. This research identifies that even though urbanization does present infrastructural development and economic development, social segregation is also on the rise, and people of lower classes and culturally sensitive facets are pushed into the boundaries. These results are significant in pointing out an understanding of urbanization not only in its physical and tangible aspects but also of its social and cultural transition. This work to some extent aids in filling the existing gap in knowledge about urbanisation in Southeast Asia vis-a-vis, policy making for sustainable development fororing H traditions and the cultural bonds inherent in these societies. Pertinently, the study suggests that there is much need to develop more contextual prudential and effective physical urban planning and design solutions in view of realizing sustainable and culturally sensitive growth in the emergent urban centres.